HDL subpopulations containing apoA-I without apoA-II (LpA-I) in patients with angiographically proven coronary artery disease. Issue 3 (March 2017) - Kuchta, Agnieszka; Strzelecki, Adrian; Ćwiklińska, Agnieszka; Gruchała, Marcin; Zdrojewski, Zbigniew; Kortas-Stempak, Barbara; Wieczorek, Ewa; Gliwińska, Anna; Dąbkowski, Kamil; Jankowski, Maciej
Abstract: Background: High density lipoproteins (HDL) can be divided into two metabolically distinct fractions, one containing apolipoprotein (Apo) A-I but not ApoA-II [apolipoprotein A-I; lipoprotein (Lp) A-I] and the other containing both ApoA-I and ApoA-II (LpA-I/A-II). LpA-I fraction which, seeming to be more cardioprotective than LpA-I/A-II particles, is itself heterogeneous. Preβ1-HDL is a minor subfraction of LpA-I and the initial acceptor of cellular cholesterol in the process of reverse cholesterol transport. The aim of the study was to determine the usefulness of the determination of LpA-I fractions as indicators for the atherosclerotic process. Methods: The study included 112 patients with angiographically-documented coronary artery disease (CAD+) and 51 patients with negative results of coronary angiography (CAD−). We evaluated LpA-I concentration in serum in HDL2 and HDL3 fractions as well as Preβ1-HDL concentration. Furthermore, we analyzed the association of the assessed parameters with the extent and severity of CAD assessed by Gensini score. Results: CAD+ patients were characterized by a lower concentration of serum LpA-I by 19%, LpA-I in HDL2 by 26%, higher level of Preβ1-HDL by 27%, and elevated Preβ1-HDL/LpA-I values by 62%. Univariate correlation analysis indicated that serum LpA-I and HDL-cholesterol concentrations were negatively correlated with Gensini score ( R = −0.279; p = 0.002, R = −0.227; p = 0.016, respectively) whereas Preβ1-HDL/LpA-I values were positively correlated with the severity of CAD ( R = 0.529; p < 0.001). In multiple linear regression, after adjusting for age, gender, preexisting hypertension, diabetes, and statin therapy, only the Preβ1-HDL/LpA-I values remained an independent determinant of atherosclerosis severity ( β = −0.499; p < 0.001). Conclusions: Our results show a lower level of LpA-I and higher concentration of Preβ1-HDL in the CAD+ patients compared to the CAD− group. We suggest that the distribution of LpA-I is different in CAD and the Preβ1-HDL/LpA-I ratio may have additional value in assessing anti-atherogenic potential of HDL particles and it is likely to become a clinically valuable indicator of atherosclerosis development.